Political Parties of the Aristocrat's Large Farm in Bohemia and Moravia 1861-1914 and theirs Relation to National Party - Krákora, Pavel (Civilia, 2012)
This study deals with the political parties of the Aristocrat's Large Farm in Bohemia and Moravia in the 2nd half of the 19th and on the beginning 20th Century considering political system in Cislaitania. The attention is also paid to application of this topic into curriculum of the history and civics.
Keywords: Political Parties; Aristocrat's large farm; Bohemia; Moravia; Cislaitania; Bohemia and Moravia Land Assembly; Curriculum; History; Civics